1987
DOI: 10.1123/ssj.4.3.213
|View full text |Cite
|
Sign up to set email alerts
|

The Social World of High School Athletic Coaches: Multiple Role Demands and Their Consequences

Abstract: A field study of high school teacher/coaches was undertaken, guided by the following general questions: What is it like being a high school teacher/coach? What are the main occupational contingencies for high school teacher/coaches? How do teacher/coaches think about themselves and their situations? The larger field study that provided the data base for this paper was conducted over a 5-month period in 1985 during which I observed teacher/coaches in six high schools. The data were drawn from naturally occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 35 publications
0
70
1
Order By: Relevance
“…When faced with role conflict, people have to make choices. Feeling forced to choose among competing roles is not a new problem, seeing that among the teacher-coaches interviewed in Sage's (1987) field research nearly thirty years ago, there was consistent agreement among the participants that they gave priority to their coaching and that as a result, their classroom preparation got shortchanged. In Paul's (1974) (2005), when juggling too many demands, some employees may feel forced to stretch their attention, effort, and resources, which could impact even high performers' estimates of their self-efficacy, acceptance of challenging personal goals, and subsequent performance levels.…”
Section: Role Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…When faced with role conflict, people have to make choices. Feeling forced to choose among competing roles is not a new problem, seeing that among the teacher-coaches interviewed in Sage's (1987) field research nearly thirty years ago, there was consistent agreement among the participants that they gave priority to their coaching and that as a result, their classroom preparation got shortchanged. In Paul's (1974) (2005), when juggling too many demands, some employees may feel forced to stretch their attention, effort, and resources, which could impact even high performers' estimates of their self-efficacy, acceptance of challenging personal goals, and subsequent performance levels.…”
Section: Role Conflictmentioning
confidence: 99%
“…In Paul's (1974) (2005), when juggling too many demands, some employees may feel forced to stretch their attention, effort, and resources, which could impact even high performers' estimates of their self-efficacy, acceptance of challenging personal goals, and subsequent performance levels. For professionals working in the field of athletics, role conflict has been examined from many perspectives, including teachercoach (Figone, 1994;Richards & Templin, 2012;Richards, Templin, Levesque-Bristol, & Blankenship, 2014;Sage, 1987) physical education teacher-athletic directors (Ha et al, 2011), and certified athletic trainerclinical instructors (Henning & Weidner, 2008). Schmidt, Roesler, Kusserow and Rau (2014) reported that role conflict leads to a psychological conflict in which employees will not be capable of fulfilling every expected role at the same time.…”
Section: Role Conflictmentioning
confidence: 99%
“…Coaches at the high schoollevel have been identified as assurning at least thirteen different roles. These include, but are not lirnited to, teacher, instructor, trainer, leader, rnotivator, substitute parent, friend, social worker, adrninistrator, mentor, manager, disciplinarian, and provider of social support (Gurnmerson, 1992;Sage, 1987;Smoll & Smith, 1996). To fulfill these various roles, coaches should possess both sport-specifie and general coaching knowledge (Abraham & Literature Review 13 Collins, 1998;Cushion, Armour, & Jones, 2003;Potrac, Brewer, Jones, Armour, & Hoff, 2000;Saury & Durand, 1998).…”
Section: High School Coachesmentioning
confidence: 99%
“…According to the CM, the goal of the coach is to develop the athlete and the team (Côté, Salmela, Trudel et al,1995), although the authors never explicitly expanded on this idea. Recent research has shown that high school ( e.g., Gould, Collins, Lauer, & Chung, 2007) (Gummerson, 1992;Sage, 1987;Clark, 2001). For instance, Sage demonstrated that high school coaching responsibilities included assuming the role of the teacher, trainer, administrator, motivator, and disciplinarian.…”
Section: Persona! and Contextual Factorsmentioning
confidence: 99%
See 1 more Smart Citation